Avaliação do volume residual gástrico por ressonância magnética após ingestão de maltodextrina e glutamina. Estudo clínico randomizado, duplo-cego, cruzado - Brianez, Luigi Rodrigues (2013)
Prolonged preoperative fasting increases insulin resistance, and intensifies the metabolic stress that occurs in surgical trauma. Actually, the abbreviation of time of preoperative fasting with beverages containing carbohydrates is recommended, based on many evidences. Protein addition in these beverages further improves the post operative recuperation. It must be questioned if the addition of more effective nutritional substance than the carbohydrate, like a glutamine, can even more modulate the immune response, without damages to the gastric emptying capacity. The objective of this study was to evaluate the gastric residual volume after intake of beverage with carbohydrate (CHO) and carbohydrate plus glutamine (CHO+GLN) using the magnetic resonance. Methods: Healthy volunteers (n=11) were randomized in a crossover study to intake 400ml and 200ml of beverage with carbohydrate (maltodextrin) and the same amount of beverage with carbohydrate and glutamine (maltodextrin + glutamine). Two hours and three hours after the intake, all volunteers were submitted to superior abdominal magnetic resonance and the gastric residual volume was measured, in milliliters (ml). A 5% level was established for significance level. Results: There was no difference in the gastric residual volume media after 120 minutes of the beverages intake in CHO and CHO+GLN groups (22,9±16,6ml vs 19,7±10,7ml p>0,05). There was no difference in the gastric residual volume media after 180 minutes of the beverages intake in CHO and CHO+GLN groups (21,5±24,1ml vs 15,1±10,1ml p>0,05). Conclusion: Both solution had similar gastric emptying (only carbohydrate or combined with glutamine). The gastric emptying occurs almost complete after 2h intake. There is no difference in the gastric residual volume among solutions.